(3ESQGA GdCSQi Edi CSQGQ MRH GdGSQGs - (3eMeO Hf GdeNJGQ Hf CMeO Hf CHj HcQ GdcfJjs
(3ChdgG (B:s
(3GdMeO ddg LdG eQBI HUGFQ GdPGcQjf ef UOC GdZadGJ CeG HYO ajbhd deG ef Gdg Ydi HGdJjSjQ hTQM GdUOhQ ddJUOi HMd CdaGX MRH GdESQG hOYhJg H` ESQGA GdCSQi s
(3BNQgG (B:s
(3hai hbJ JYQV Edjg LHQjd , abGd (B: (3Cdc MGLI ? abGd (B: (3CeG Edjc adG , hCeG Edi Gddg aHdi , bGd (B: (3Sdg , bGd (B: (3Ydeg HMGdi s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV YHGQJgG HGdMeQIs
(3ChQGbgG eJbUaIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs